Ritual and religion in the making of humanity - Rappaport, Roy A. (Cambridge, Cambridge University Press., 1999)
Roy Rappaport argues that religion is central to the continuing evolution of life, although it has been displaced from its original position of intellectual authority by the rise of modern science
Foreword / Keith Hart -- 1. Introduction -- 2. The ritual form -- 3. Self-referential messages -- 4. Enactments of meaning -- 5. Word and act, form and substance -- 6. Time and liturgical order -- 7. Intervals, eternity, and communitas -- 8. Simultaneity and hierarchy -- 9. The idea of the sacred -- 10. Sanctification -- 11. Truth and order -- 12. The numinous, the Holy, and the divine -- 13. Religion in adaptation -- 14. The breaking of the Holy and its salvation
Includes bibliographical references (pages 499-518) and index
Keywords: Ritual; Religion; Anthropology of religion; Ceremonial Behavior; Religion